Shifted intrinsic connectivity of central executive and salience network in borderline personality disorder - Doll, Anselm; Sorg, Christian; Manoliu, Andrei; Meng, Chun; Wöller, Andreas; Förstl, Hans; Zimmer, Claus; Wohlschläger, Afra; Riedl, Valentin (Frontiers in Human Neuroscience, 2013)
Borderline personality disorder (BPD) is characterized by “stable instability” of emotions and behavior and their regulation. This emotional and behavioral instability corresponds with a neurocognitive triple network model of psychopathology, which suggests that aberrant emotional saliency and cognitive control is associated with aberrant interaction across three intrinsic connectivity networks (ICN) (i.e. the salience, default mode, and central executive network, SN, DMN, CEN). The objective of the current study was to investigate whether and how such triple network intrinsic functional connectivity (iFC) is changed in patients with BPD. We acquired resting-state functional magnetic resonance imaging (rs-fMRI) data from fourteen patients with BPD and sixteen healthy controls (HC). High-model order independent component analysis (ICA) was used to extract spatiotemporal patterns of ongoing, coherent blood-oxygen-level-dependent (BOLD) signal fluctuations from rs-fMRI data. Main outcome measures were iFC within networks (intra-iFC) and between networks (i.e. network time course correlation inter-iFC). Aberrant intra-iFC was found in patients’ DMN, SN, and CEN, consistent with previous findings. While patients’ inter-iFC of the CEN was decreased, inter-iFC of the SN was increased. In particular, a balance index reflecting the relationship of CEN-and SN-inter-iFC across networks was strongly shifted from CEN to SN connectivity in patients. Results provide first preliminary evidence for aberrant triple network intrinsic functional connectivity in BPD. Our data suggest a shift of inter-network iFC from networks involved in cognitive control to those of emotion-related activity in BPD, potentially reflecting the persistent instability of emotion regulation in patients.